Pengaruh Beban Kerja dan Kesejahteraan Psikologis Terhadap Kinerja Karyawan Dengan Work-Life Balance Sebagai Peran Mediasi pada Telkom Witel SULBAGSEL - Santika, Delin; Haeruddin, M. Ikhwan Maulana; Kurniawan, Agung Widhi; Dipoatmodjo, Tenri S.P.; Abadi, Rahmat Riwayat (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
This study examines the influence of workload and psychological well-being on employee performance with work-life balance as a mediating variable among employees of Telkom Witel South Sulawesi Region. The research employed a quantitative approach with an associative design by distributing questionnaires to 75 respondents. Data were analyzed using Structural Equation Modeling (SEM) assisted by SmartPLS 4. The results indicate that workload has a positive and significant effect on employee performance, while psychological well-being shows a positive but insignificant effect. Both workload and psychological well-being have a positive and significant effect on work-life balance. However, work-life balance is unable to mediate the effect of workload or psychological well-being on employee performance. These findings highlight that employee performance is more strongly influenced by direct work demands and psychological well-being rather than through the mechanism of work-life balance.